Workforce development in the trucking industry: A comprehensive analysis of truck driver training entities - Sicheng Wang; Elizabeth A. Mack; Nidhi Kalani; Chu-Hsiang Chang; Shelia R. Cotten (Transport Economics and Management)
The transformation of transportation technologies, economic structures, and social lifestyles is changing the truck-driving workforce. Recognizing the trends and challenges of the job is essential for proactive planning to address potential disruptions in the trucking industry and the broader economy. Despite the importance of truck drivers, the research community has little information about the entities involved in training truck drivers. These entities are critical in creating a pipeline of drivers to address the driver shortage issue and respond to the changing requirements of drivers. To address this knowledge gap, we utilize institutional theory as a framework to disentangle the factors that affect entities' considerations behind the design and delivery of driver training programs. Using explanatory sequential mixed methods, we collect and analyze multiple sources of data about driver training, including information about the entities providing training, as well as information about funding and federal regulations. In-depth interviews with these entities provide additional insights into the process of training drivers and how it varies between different types of training entities. Analytical results indicate that regulatory changes have impacted the number and types of entities providing driver training. A qualitative analysis of the interviews reveals different business models for training drivers, as well as the advantages and disadvantages of these models in terms of cost to the trainee, time to completion, and coordination costs. Finally, we discuss the implications of our findings for policymaking, including workforce development, transportation safety, and preparation for technological change.